Correlação de perfis geofísicos de poços: sede do município de Salinópolis - PA - FREIMANN, Boris Chaves (2019)
It was realized a correlation of geophysical well logs from the Sanitation Company of Pará (COSANPA) drilled in the city of Salinópolis for the local supply. The study was conducted in many areas of impound, covering 15 wells. The parameters used in the correlation were Self Potential (SP), Electrical Resistivity (ER) and Gamma Ray (GR). Also, for control purposes, was used the lithological log of the wells obtained from samples of drill cutting. This correlation was conducted to evaluate the lateral continuity of permeable and impermeable layers, in order to develop sections of the subsurface with high accuracy. It was found the probable existence of two major aquifers that lie 60 meters below sea level and have lateral continuity along the full extent of the studied area. It was also found that the top of the basement in the studied area is around 120 meters below sea level. These findings are extremely important for a better location and constructive evaluation for supply wells in the future projects in the city of Salinópolis-Pa.